2017
DOI: 10.17267/2317-3386bjmhh.v5i4.1379
|View full text |Cite
|
Sign up to set email alerts
|

Exercises With and Without Virtual Reality on Pain in Patients With Parkinson Disease: A Randomized, Controlled, Single-Blind Trial

Abstract: Introduction: Pain in individuals with Parkinson's Disease (PD) may result from factors such as progressive changes of the disease, originating from the Central Nervous System (CNS), until coming from classic symptoms such as stiffness, dyskinesia and dystonia, having possible correlations with important functional markers such as balance and gait. There is no consensus with regard to the treatment of pain in this condition, and exercises associated with virtual reality (VR) may be an effective intervention. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Moreover, it is stated that video games with virtual reality (VR) can be a good alternative to increase motivation and thus increase the physical activity (Segura‐Ortí & García‐Testal, 2019; Zhou et al, 2020). Studies comparing VR‐ and non‐VR‐based exercises indicated that VR‐based exercise is more effective on physical function than non‐VR‐based exercise (d'Alencar et al, 2017; Ko et al, 2020; Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is stated that video games with virtual reality (VR) can be a good alternative to increase motivation and thus increase the physical activity (Segura‐Ortí & García‐Testal, 2019; Zhou et al, 2020). Studies comparing VR‐ and non‐VR‐based exercises indicated that VR‐based exercise is more effective on physical function than non‐VR‐based exercise (d'Alencar et al, 2017; Ko et al, 2020; Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%